To find the equation of the line passing through the points (-3, 4) and (-6, 3), we can first find the slope of the line.
The formula to find the slope of a line passing through two points (x₁, y₁) and (x₂, y₂) is:
slope = (y₂ - y₁) / (x₂ - x₁)
Let's use the points (-3, 4) and (-6, 3) to calculate the slope:
slope = (3 - 4) / (-6 - (-3))
slope = -1 / (-6 + 3)
slope = -1 / (-3)
slope = 1/3
Now that we have the slope, we can use the point-slope form of a linear equation to find the equation passing through the point (-3, 4):
y - y₁ = m(x - x₁)
where m is the slope and (x₁, y₁) is a point on the line. Plugging in the values:
y - 4 = (1/3)(x - (-3))
y - 4 = (1/3)(x + 3)
To put the equation into slope-intercept form, we will isolate y:
y - 4 = (1/3)x + 1
y = (1/3)x + 1 + 4
y = (1/3)x + 5
Therefore, the equation of the line passing through the points (-3, 4) and (-6, 3) in slope-intercept form is y = (1/3)x + 5.
What is the equation of the line that passes through the points (−3,4) and (−6,3) ? Write the answer in slope-intercept form.
1 answer